PRODUCTION OF OXYTETRACYCLINE BY DIFFERENT MUTANTS OF STREPTOMYCES RIMOSUS INDUCED BY DRY AND WET HEAT IN A DATE MEDIUM (Biological Sciences - PJSIR, 2022)
Dry heat was more effective as physical mutagen than wet heat for Streptomyces rimosus. The optimal dose oftemperaturefor inducing auxotrophic mutants in Streptomyces rimosus was 55° under dry treatment conditions. Twomutants only out of 138 dry and wet heat mutants produced higher antibiotic titres than the parent organism.